2002
DOI: 10.1109/tmag.2002.803568
|View full text |Cite
|
Sign up to set email alerts
|

Statics and dynamics in giant magnetostrictive Tb/sub x/Fe/sub 1-x/-Fe/sub 0.6/Co/sub 0.4/ multilayers for MEMS

Abstract: In the present paper, giant magnetostrictive thin films have been investigated for future microelectromechanical systems (MEMS) purposes. For this goal, flexural and torsional motions have been studied in low field anisotropic giant magnetostrictive (GMS) single domain state (SDS) exchange-coupled TbFe/FeCo multilayers (ECML). The magnetoelastic (ME) coefficient b γ,2 depend strongly on the ECML structures, compositions, and sputtering deposition parameters. Giant magnetostrictive Multilayers with a high b γ,2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…7 In 2010, we proposed and patented an innovative memory device called MELRAM (Magneto-ELectric Random Access Memory) based on a composite structure composed of a nanometer sized magnetostrictive material embedded in a piezoelectric matrix. [8][9][10][11] In particular, we showed that the competition between an external magnetic field and uni-axial magnetic anisotropy can be used to define two perpendicular equilibrium positions for magnetization 12,13 and that the application of stress can trigger the switch between both positions in a deterministic fashion. A macroscopic device using a commercial piezoelectric stack provided an experimental proof of concept of this memory element 14 and demonstrated the writing principle using piezoelectric stress.…”
mentioning
confidence: 99%
“…7 In 2010, we proposed and patented an innovative memory device called MELRAM (Magneto-ELectric Random Access Memory) based on a composite structure composed of a nanometer sized magnetostrictive material embedded in a piezoelectric matrix. [8][9][10][11] In particular, we showed that the competition between an external magnetic field and uni-axial magnetic anisotropy can be used to define two perpendicular equilibrium positions for magnetization 12,13 and that the application of stress can trigger the switch between both positions in a deterministic fashion. A macroscopic device using a commercial piezoelectric stack provided an experimental proof of concept of this memory element 14 and demonstrated the writing principle using piezoelectric stress.…”
mentioning
confidence: 99%
“…Another approach for magnetostrictive actuators is the vertical stacking of materials with different magnetostrictive coefficients (multilayers) to gain an out-of-plane deflection in presence of a magnetic field. These actuators can be designed to exhibit small dimensions by utilizing microfabrication technologies, but lack of high stroke displacements and blocking forces [8], [9].…”
Section: Icroelectromechanical System (Mems)mentioning
confidence: 99%
“…In this last approach, the goal is to enhance the sensitivity of the actuator to the driving field by taking profit of the magnetic instability. It is also possible to propose new strategies of actuation based on dynamic properties of the system in the vicinity of the SRT [11,12].…”
Section: Introductionmentioning
confidence: 99%